ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STUNTING PADA BALITA DI KOTA GORONTALO MENGGUNAKAN REGRESI BINOMIAL NEGATIF - ZUBEDI, FAHREZAL; ALIU, MUFTIH ALWI; RAHIM, YOLANDA; OROH, FRANKY ALFRITS (Department of Mathematics, Universitas Negeri Gorontalo, 2021)
This study aims to model stunting cases in children under five in Gorontalo city in 2018. In this model, it can be seen that the significant factors that affect stunting cases in children under five in Gorontalo city in 2018. This study uses data on stunting cases in 9 (nine) districts in the city of Gorontalo and the factors that influence it. The research data were obtained from the Public Health in Gorontalo city. This study used one response variable, namely the number of cases of stunting and four predictor variables, namely number of toddlers who received exclusive breastfeeding, the percentage of low birth weight (LBW), the percentage toddlers who received complete basic immunization, and number of proper sanitation. The results obtained were the variables of number of toddlers who received exclusive breastfeeding and the percentage toddlers who received complete basic immunization which had a significant effect on stunting cases in children under five in the city of Gorontalo in 2018. This was indicated by the P-value of the variable for number of toddlers who received exclusive breastfeeding of 0.00283 and P-value of variable the percentage toddlers who get complete basic immunization is 0.06564.